Análise "in vitro" da microinfiltração em retrobturação, utilizando diferente materiais retrobturadores e a influência da aplicação da Edta na cavidade retrógrada - Pelissari, Carlos Antonio (2004)
Although reaching high success rates there is a great number of root canals endodontically treated which don’t reach the wished results. In these cases there is necessity to indicate the periapical surgery. Among the surgical kinds the most used is the conventional retrograde filling. This surgical modality has also impelled the main researches about the matter.The present study had the purpose to evaluate “in vitro”the microleakage when were used some retrofilling materials and also the influence of application of EDTA in the retrograde cavity before to be filled the canals. They were used in this study seventy two mandibular and maxillary human canine teeth extracted for several reasons in Surgical Clinic of State University – Ponta Grossa – Pr – Brazil. Initially all teeth were instrumented and filled according to traditional technics of preparation and filling. After this the teeth had the apical portion sectioned perpendicularly to tooth long axis and its external surface was made waterproof. After the apicectomy they were prepared cavities of approximately 3 mm deep using the sonic equipment GNATUS ( JET- SONIC FOUR) with the point S12 with the angle of 90 with the active point with diamond with 3 mm long and a caliber compatible to the most of teeth. The seventy two teeth were fortuitously distributed in six groups with twelve teeth each one according to the materials to be used. In three groups before the retrograde filling it was made an application of EDTA during 3 minutes in retrograde cavity. According to the procedures and the materials used in retrofillings the six groups were so constituted: Group I – retrofilling with Sealapex+zinc oxide eugenol; Group II – retrofilling with IRM; Group III – retrofilling with MTA; Group IV – application of EDTA and retrofilling with Sealapex+zinc oxide eugenol; Group V – application of EDTA and retrofilling with IRM; Group VI – application of EDTA and retrofilling with MTA. After the operative procedures and drying of the roots these were imersed in 2 methilene solution during sixty hours at 37C. After this period the roots were washed in current water during 12 hours and the proofing layer was removed. It was performed them the longitudinal wearing of the root till the exposition of the retrofilling material making possible the analysis of the leakage. To verify the extension of the leakage the teeth were photographed with digital camera and the images transported to the computer where they were analysed in a specific program called Mocha to measure the apical microleakage. The leakage was measured from a root end to the more depth of leakage observed. The values of the leakages of each tooth in milimeters and the overages of the leakages were duly ordered and submited to the statistical analysis from which we conclude: There wasn’t influence when it was applicated the EDTA in retrograde cavity before the use of the retrofilling materials evaluated; There are statistically significative differences when the groups of retrofilling materials were compared and when the application of EDTA alone was analysed; The retrofilling material IRM presents the most degree of marginal leakage; MTA was shown to be the best among the evaluated materials; Sealapex+zinc oxide eugenol didn’t present significative difference in relation to MTA; EDTA used in retrograde cavity increased the degree of microleakage.